Customer Perception towards Adoption of e-banking Services in Kathmandu: A Survey of Business School Students - Sthapit, Arhan; Bajracharya, Nirmal (Journal of Business and Social Sciences Research, 2019)
This paper aims to examine the association between the perception of business school students and their adoption of e-banking services. This study integrates Technology Acceptance Model (TAM) and perceived risk to explain the adoption of e-banking. The study measures customer perception towards the adoption of e-banking services in terms of a) perceived usefulness, b) ease of use and c) perceived risks. Based on descriptive and causal research designs, the study made use of primary data collected through a structured questionnaire surveyed successfully on 159 business school students. By using descriptive statistics, t-test, correlation and regression, the study discovered that customer perception of usefulness, ease of use and risks have impacted on the adoption and use of e-banking services. Among the three perception variables measured, perceived usefulness made the strongest influence on business students’ adoption of e-banking in Kathmandu. The study findings should prove instrumental in formulating e-banking strategies targeted at Generation Z (Post-Millennials or iGeneration) and Millennials.